Visual Rounds Based on Multiorgan Point-of-Care Ultrasound in the ICU - Mao, Jia-Yu; Zhang, Hong-Min; Liu, Da-Wei; Wang, Xiao-Ting (Frontiers in Medicine, 2022)
Point-of-care ultrasonography (POCUS) is defined as the acquisition, interpretation, and immediate clinical integration of ultrasonographic imaging performed by a treating clinician at the patient’s bedside rather than by a radiologist or cardiologist. The use of POCUS is not limited to one specialty, protocol, or organ system. POCUS provides the treating clinician with real-time diagnostic and monitoring information. Visual rounds based on multiorgan POCUS act as an initiative to improve clinical practice in the Intensive Care Unit and are urgently needed as part of routine clinical practice.